The impact of social media on B2B brands - Blatská, Veronika (2023)
The thesis is focused on B2B branding and what impact social media have on B2B branding. The theoretical part is divided into two parts. In the first part, the concept of B2B branding, the role of B2B brands, B2B brand architecture and building a B2B brand are explained. The second part includes the topics social media used in B2B branding, the usage of multiple social media platforms and the use of social media in B2B branding. The practical part of the thesis focuses on the research of the use and influence of social media in brand building through in-depth interviews and subsequent evaluation of the research results.